Evaluation of Umbilical Vein Blood Volume Flow in Preeclampsia by Angle‐Independent 3D Sonography. (15th December 2017) - Pinter, Stephen Z.; Kripfgans, Oliver D.; Treadwell, Marjorie C.; Kneitel, Anna W.; Fowlkes, J. Brian; Rubin, Jonathan M.
Abstract : Objectives: To investigate the association between umbilical vein blood volume flow and the condition of preeclampsia in an at‐risk maternal patient cohort. Umbilical vein volume flow was quantified by a 3‐dimensional (3D) sonographic technique that overcomes several limitations of standard sonographic flow measurement methods. Methods: A total of 35 patients, each with a singleton pregnancy, were recruited to provide 5 patients with preeclampsia, derived as a subset from a 26‐patient at‐risk group, and 9 patients with normal pregnancies. An ultrasound system equipped with a 2.0–8.0‐MHz transducer was used to acquire multivolume 3D color flow and power mode data sets to compute the mean umbilical vein volume flow in patients with normal pregnancies and preeclampsia. Results: The gestational ages of the pregnancies ranged from 29.7 to 34.3 weeks in the patients with preeclampsia and from 25.9 to 34.7 weeks in the patients with normal pregnancies. Comparisons between patients with normal pregnancies and those with preeclampsia showed weight‐normalized flow with a moderately high separation between groups ( P  = .11) and depth‐corrected, weight‐normalized flow with a statistically significant difference between groups ( P  = .035). Umbilical vein volume flow measurements were highly reproducible in the mean estimate, with an intrapatient relative SE of 12.1% ± 5.9% and an intrameasurement relative SE of 5.6% ± 1.9 %. In patients who developed pregnancy‐induced hypertension or severe pregnancy‐induced hypertension, umbilical vein volume flow suggested gestational hypertensive disorder before clinical diagnosis. Conclusions: Results indicate that mean depth‐corrected, weight‐normalized umbilical vein volume flow is reduced in pregnancies complicated by preeclampsia and that volume flow may indicate hypertensive disorder earlier in gestation. Volume flow measurements are highly reproducible, and further study in a larger clinical population is encouraged to determine whether 3D volume flow can complement the management of preeclampsia and, in general, at‐risk pregnancy.